Desert greens: Unveiling the antioxidant power and health benefits of Qatar's locally grown leafy vegetables - AlNasr , Mashael; Salam , Hanan; Al-Kendi, Aldana; AlAbdi , Tamara; Ahmed, Abdelhakam Esmaeil Mohamed; Mukarram, Shaikh Ayaz; Kovács, Béla; ElObeid , Tahra (Acta Agraria Debreceniensis, 2025)
The long-term consumption of diets rich in plant polyphenols has a high potential to reduce the risk of chronic diseases such as cancer, cardiovascular disease, and diabetes. This study focuses on the phenolic and antioxidant properties of eight green leafy vegetables, red spinach, green spinach, water spinach, chives, rocca, Swiss chard, jute mallow, and purslane, commonly cultivated in Qatar. Antioxidant capacity (AC) was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method. The total phenolic content (TPC) of the samples was quantified using the Folin-Ciocalteu assay. Among all the vegetables, results indicated significant differences among all examined values at level of 5% Jute Mallow exhibited the highest phenolic content at 205.39±11.50 mg GA/100g, followed by Green Spinach at 189.58±10.56 mg GA/100g and Red Spinach at 185.15±2.93 mg GA/100g. Swiss chard exhibited the highest antioxidant activity of 89.26%. This study provides valuable data on these vegetables to positively affect the health and well-being of the population. Intensifying further future investigation to embrace a wider phytochemical profile (e.g., flavonoids, carotenoids, vitamin C), varied antioxidant assays (e.g., FRAP, ABTS), and bioavailability tests would expand the understanding of the studied leafy vegetables health benefits.